PENGGUNAAN JARGON BAHASA OLEH DRIVER GRAB MALANG DALAM GRUP WHATSAPP - Anisa Ayu Fitnia; Rahutami Rahutami; Tatik Swandari (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2020)
Driver Grab has a special word (jargon) to communicate in groups. This study aims to describe the form and meaning of Grab driver jargon. This research uses descriptive qualitative method because the analyzed data are in the form of words and phrases from the Grab Malang whatsapp driver group. The results showed that driver grab jargon has two forms of lingual units, while the meaning of jargon has two meanings. The lingual unit form consists of words and phrases with. Word forms refer to activities, greetings, nouns, place nouns, and circumstances. Phrase form refers to activities, greetings, place nouns, and circumstances. Whereas the meaning of jargon consists of literal meaning and contextual meaning. The use of language jargon in the Grab whatsapp driver group is done to make communication more effective and differentiate with the community outside the driver group and to provide easier language access for new members in the Grab Malang whatsapp driver group.